Exploring the Impact of Gamification and Flipped Classroom in Teaching Administration and Management in Nursing: A Case Study - Estefania Coello Gonçalves Canedo (Colegio de Enfermería de Caceres, 2024)
Background: Learning administration and management as a curricular unit is a great challenge for both students and teachers. The current generation of students is very different from the previous generation, and they are equipped to process information in diverse ways, which should be effectively utilized by undergraduate teachers. To observe and analyze the possible relationship between pedagogical methodologies, gamification, and flipped classroom, and the development of critical and reflective thinking, promoting learning from a constructivist perspective. Additionally, we examined students' perceptions of discipline using these methodologies. Method: A case study was conducted using a mixed-method approach, combining phenomenological and reflective research, and integrating qualitative and quantitative methods. Results: A syllabus was developed and structured according to the curriculum division into theoretical and practical classrooms, and pedagogical methodologies were adapted for the content. The results demonstrated student satisfaction regarding the use of new methodologies and technological innovation in teaching. Conclusion: There seems to be a positive relationship between the use of gamification and flipped classroom and the development of critical and reflective thinking. The introduction of new educational methodologies increased students' motivation and interest in the discipline, indicating a positive perception. However, further reflection, study, and research are needed to enhance the discipline's pedagogical strategy, considering its theoretical framework and practical applicability.